Dynamic transmission and evolutionary analysis of the HIV-1 subtype CRF01_AE pol region in Ningxia, China - Ziyang Luo; Wei Sun; Jianxin Pei; Subinuer Mutalifu; Youping Duan; Yufeng Li; Xiaohong Zhu; Zhonglan Wu (PLoS ONE, 2026)
The CRF01_AE recombinant is the dominant HIV strain in Ningxia, characterized by rapid disease progression and imposing a significant local burden. Current prevention strategies, often based on broad subtype classifications, are insufficient to address the distinct transmission dynamics of such specific recombinants. To delineate the spatiotemporal migration patterns and epidemic trends of CRF01_AE in Ningxia, this study conducted a systematic analysis of 206 local sequences. The results reveal extensive viral spread with clear geographic diffusion routes, particularly strong migration from Yinchuan to other major cities. Key demographic groups driving transmission are individuals aged 20–39, retired/unemployed persons, and those with junior high school education. Although the transmission intensity has fluctuated, the current effective reproductive number remains above 1, indicating ongoing epidemic expansion, while the viral evolutionary rate appears stable. The study demonstrates that the CRF01_AE epidemic in Ningxia is still expanding and evolving, and identifies core transmission hubs and population clusters. These findings not only align with some prior understanding but also uncover more complex transmission networks and demographic patterns, highlighting the necessity for implementing targeted interventions specific to this strain to effectively control its spread.